“A Study Of Fixed Point Theory In Banach Spaces” (Journal of Pharmaceutical Negative Results, 2023)
In this paper we list some geometric properties of Banach spaces and some fixed point theory results which we use in the subsequent topic . Certain geometric properties of a Banach space X are helpful to study the existence of fixed points for non expansive mappings and asymptotically non expansive mappings on closed bounded convex subsets of X. In this paper first we give a brief introduction to Geometry of Banach spaces, a brief introduction to fixed point theory, a brief introduction to best proximity point theorems, and finally we give contents of the paper.